y = mx + c اور ax + کے ذریعہ + c = 0 کے درمیان بنیادی فرق کیا ہے؟ ہم ان دونوں مساوات کو کس طرح جوڑ سکتے ہیں؟


جواب 1:

Linearequationintheformy=mx+c,ismorestraightforward.The[math]m[/math]isthegrade/slopeoftheline,andthe[math]c[/math]isitsintersectionwithyaxis.Linear equation in the form y=mx+c, is more straightforward. The [math]m[/math] is the grade/slope of the line, and the [math]c[/math] is it's intersection with y-axis.

Whilestraightforward,itsometimesmaylookugly",whenmand/or[math]c[/math]arefractions,andwouldmakeitevenhardertosolveasystemoflinearequations.While straightforward, it sometimes may look “ugly", when m and/or [math]c[/math] are fractions, and would make it even harder to solve a system of linear equations.

Forexampletheequationy=23x34islesselegant"comparedto[math]8x12y9=0[/math];altoughbotharethesame.Andthelaterwillbeeasiertoprocessinsystemofequations.For example the equation y=\frac{2}{3}x-\frac{3}{4} is “less elegant" compared to [math]8x-12y-9=0[/math]; altough both are the same. And the later will be easier to process in system of equations.

Therelationbetweenoneform(Ax+By+C=0)andtheother([math]y=mx+c[/math]),couldbeshownhere:The relation between one form (Ax+By+C=0) and the other ([math]y=mx+c[/math]), could be shown here:

Ax+By+C=0Ax+By+C=0

Ax+By+CAxC=0AxC(SubstractAxandCfrombothsides)Ax+By+C-Ax-C=0-Ax-C (Substract Ax and C from both sides)

By=AxCBy=-Ax-C

BBy=ABxCB(DividebothsidewithB)\frac{B}{B}y=-\frac{A}{B}x-\frac{C}{B} (Divide both side with B)

y=ABxCB=mx+cy=-\frac{A}{B}x-\frac{C}{B}=mx+c

Thus,whentheformisAx+By+C=0,thentheslope[math]m=AB[/math]anditsintersectionwithyaxis[math]c=CB[/math].Thus, when the form is Ax+By+C=0, then the slope [math]m=-\frac{A}{B}[/math] and its intersection with y-axis [math]c=-\frac{C}{B}[/math].

Toconvertfromy=mx+cto[math]Ax+By+C=0[/math]youneedtomoveeverthingfromLHStoRHSorviceversaandmultiplybothsidewithsomenumberthat(preferably)willmakeallfractionintointegerandcoefficientofxispositive.ThisisussuallytheLeastCommonMultipleofthedenominators.Example:To convert from y=mx+c to [math]Ax+By+C=0[/math] you need to move everthing from LHS to RHS or vice versa and multiply both side with some number that (preferably) will make all fraction into integer and coefficient of x is positive. This is ussually the Least Common Multiple of the denominators. Example:

y=23x34y=\frac{2}{3}x-\frac{3}{4}

12y=12(23x34)(MultiplybothsideswithLCMof3and4thatis12)12y=12(\frac{2}{3}x-\frac{3}{4}) (Multiply both sides with LCM of 3 and 4 that is 12)

12y=12×23x12×3412y=12×\frac{2}{3}x-12×\frac{3}{4}

12y=8x912y=8x-9

12y12y=8x912y(Substract12yfronbothsides)12y-12y=8x-9-12y (Substract 12y fron both sides)

0=8x912y0=8x-9-12y

8x12y9=08x-12y-9=0

y=ABxCB=mx+cy=-\frac{A}{B}x-\frac{C}{B}=mx+c

اس طرح ، جب فارم ہے

Ax+By+C=0Ax+By+C=0

,thentheslopem=ABanditsintersectionwithyaxis[math]c=CB[/math]., then the slope m=-\frac{A}{B} and its intersection with y-axis [math]c=-\frac{C}{B}[/math].

سے تبدیل کرنا

y=mx+cy=mx+c

toAx+By+C=0youneedtomoveeverthingfromLHStoRHSorviceversaandmultiplybothsidewithsomenumberthat(preferably)willmakeallfractionintointegerandcoefficientofxispositive.ThisisussuallytheLeastCommonMultipleofthedenominators.Example: to Ax+By+C=0 you need to move everthing from LHS to RHS or vice versa and multiply both side with some number that (preferably) will make all fraction into integer and coefficient of x is positive. This is ussually the Least Common Multiple of the denominators. Example:

y=23x34y=\frac{2}{3}x-\frac{3}{4}

12y=12(23x34)12y=12(\frac{2}{3}x-\frac{3}{4})

 (دونوں اطراف کو 3 اور 4 کے ایل سی ایم سے ضرب کریں جو 12 ہے)

12y=12×23x12×3412y=12×\frac{2}{3}x-12×\frac{3}{4}

12y=8x912y=8x-9

12y12y=8x912y12y-12y=8x-9-12y

 (دونوں فریقوں کو 12y فرنٹ)

0=8x912y0=8x-9-12y

8x12y9=08x-12y-9=0


جواب 2:

ہوائی جہاز میں لائنوں کے ل They وہ دونوں مساوات ہیں۔ لیکن دوسری شکل قدرے زیادہ عمومی ہے کیونکہ یہ عمودی لائنوں کی اجازت دیتی ہے ، ایسی صورت میں جو b = 0 ہے۔ اگر b دوسری شکل میں صفر نہیں ہے تو ، پہلی شکل اسے = -ax - c کے بطور لکھ کر اور b کے ذریعہ تقسیم کرکے حاصل کی جاسکتی ہے ، تاکہ اسے y = (-a / b) x + (-c / b)


جواب 3:

امریکہ میں ، y = mx + c کو لکیر اور کلہاڑی + مساوی + مساوی کی مساوات کی شکل کو "ڈھال سے روکنے" کہا جاتا ہے جسے "معیاری" شکل کہا جاتا ہے (ایسی ضرورت کے ساتھ جو مثبت ہے؟)۔ کلاس + بائی + سی = 0 معیاری فارم میں صرف ایک تغیر ہے ، اگرچہ اس میں معیاری فارم کے ساتھ دوسرے مستقل مزاج کے ساتھ مستقل مزاجی آتا ہے۔

ریاضی اساتذہ طلباء کو ایک دوسرے سے دوسرے میں تبدیل کرکے تشدد کا نشانہ بناتے ہیں۔

آپ "الجبرا کرکے" ایک سے دوسرے میں تبدیل ہو سکتے ہیں۔

کلہاڑی + بہ + c = 0؛ کلہاڑی دیتے ہوئے دونوں اطراف سے سی کو گھٹانا = بذریعہ = -c؛ دونوں طرف سے گھٹانا b کو دونوں طرف تقسیم کریں (اس بات کی نشاندہی کریں کہ b 0 نہیں ہے) y = (-a / b) + (-c / b)۔ تو ، کلہاڑی + بہ + c = 0 کے ساتھ ، لائن کی ڈھال -a / b ہے اور y- انٹرسیپٹ -c / b ہے۔